Natal como destino turístico : um estudo das imagens (re)veladas pela mídia, pelos turistas e suas implicações educacionais e culturais - Souza, Maria de Fátima Araújo Costa de (2008)
This thesis is a result of a research on Natal/RN as a tourist destination. We understand that cities are chosen as tourist destinations beyond its cartographic localization, from other dimensions of meanings that, in its set, constitute images. These images are, probably, very different of the images constructed by native and resident populations, who possess relations of identity with the place. The knowledge of the meanings that others attribute to this city as tourist destination, bring us near to the symbolic bonds established by individuals or social groups on the act of their choices, as well as bring us near to the interaction process city-tourists where the expectations are confirmed or not. The images divulgated by the media also participate of the complex formation of the tourist image that is being constructed and available for the different public, in different social contexts. The tourism constitutes a symbolic asset of the modern society, being considered by the studious, as one of the most expressive phenomena of the modernity, for involving each year displacement and the interaction of thousand of people of different cultures in the entire world. All this people s mobilization points to practical social related to personal motivations, to the entailed desired to the idea to travel and to exceed borders. It is already consensus that tourism is a phenomenon of economic growth, generating jobs, income, professional, qualification, bringing improvements for the host cities. Since 1995, in Brazil, the tourism as a sector of the economy, passed to be considered one of the national priorities, and in this perspective, the national politics of the tourism invested in infrastructure of Brazilian cities with high tourist potential, objecting to increase the flows of Brazilian and foreign tourists. Owing to this fact, the country still invests in programs of tourist marketing, mainly divulging the images of the natural beauties of Brazil abroad. And for Brazilians, the campaigns appeal to rescue the feeling to be Brazilian, associating the idea to travel and know its country. Natal city possesses an excellent positioning in the tourist marketing, being predominantly divulgated in national and international level, for its naturalistic singularity, where the images of its natural enchantments as warm water beaches, white dunes, warm weather, constant breeze and an always blue sky are shown as the favorite scene on this city. From what was viewed above that the choice of a tourist destination articulates from a determined imaginary of a place, already constructed or in process of construction, we consider the knowledge of this imaginary a basic learning for the population of the city and especially, for educators, in the formation of professionals in this area and for tourism managers, elaborators of public politics. Based on this estimative, we developed this research that had as a general objective to identify the images that illustrate Natal city as a tourist destination - our objective of study, particularly the meanings and senses attributed by the tourist marketing (hotel s folders) and by the tourists that visited the city during this study. The discussions and reflections that had guided this research had been given from the theoretical link between imaginary and social representation, also considering some interfaces between the fields of communication and symbol. From the studied authors, Baczko (1985) clarifies that the study of social imaginary is directed for the mechanisms and structures of the social life, especially for the intervention accomplishes and efficient of the representations and symbols in the practical collectives, as well as in its direction and orientation . Following this same thought, Moscovici (1978) says that the social representation are produced in communicational and symbolic contexts, and these representations once that already constituted circulate socially as almost tangible entities. Based on this fundament and on the analyze of Barthes (1990), particularly in the approach given to the reading of photographic image, we could observe on hotel s folders that each page evidences senses and meanings of functionality of internal and external spaces, pointing to the way of leisure offered by the keepers of city which is the hotels. About, the leisure that they offer, it is directed to young public, giving meaning to the young myth of personalized leisure tourism on children, young and adults images. The image about security that hotels offer and the singular image of Natal city as a paradise place, provide an idealization of pleasure through the sun, dunes, and beaches and also due to the hospitability of the natives who are assigned as educated . For the tourist that participated on this research, Natal city is tied only by the imaginary of leisure and nature which constitute the emotional link of the relation media-city-tourist. And with such force and fullness of directions the city discloses without tensions and contradictions as a place protected by a mythical and sacred aura. The study also demonstrates us that the potiguar culture remains (almost) forgotten, due to the silenced in this imaginary. In this perspective, we highlight that this culture silence is very close related to the disvalue of education in its general meaning. We defend that the imaginary apprehended constitutes a new reading and a new looking and understanding the tourist reality that comes historically consolidating in this city. In this direction, we glimpse that this study and its future dismemberments can collaborate with the process of rescue the cultural values of the potiguar people, in the way that the meaning of tourist may be redefined, and the tourist image of the city can be also disclosed for its identities particularities of its culture